Efectos auditivos del ruido producido por el trafico aéreo del aeropuerto internacional El Dorado en las poblaciones de Engativa y Fontibón (2004)
ABSTRACT: The study was conducted to assess the impact of air traffic noise on the hearing conditions of the residents in the neighborhood of the airport. Materials and methods: a cross-sectional design was applied based on random population samples of scholars and adults exposed and non-exposed to such noise. A level of 65 dB(A) Ldn or more in the house, or one of 85 dB(A) Lmax or SEL individually considered was defined as the criterion for exposure. In order to examine the hearing conditions of the participants a tonal laminar audiometry was performed, and the analysis was conducted according to ELI and Larsen indexes, and in the dB reduction of the hearing threshold. The crude prevalence of hearing loss in the people exposed was compared to that in the non-exposed, and a logistic model was constructed to adjust the comparison by multiple variables. Results: according to ELI extended (6.000 hertz) and Larsen indexes, prevalence of hearing loss was significantly higher among scholars and adults exposed than in the non-exposed, with 43 and 15% higher prevalence in scholars, respectively, and 32 and 11% in adults; also, according to ELI index (4.000 hertz), prevalence among adults exposed was 3% higher than that one among the non-exposed. In addition, threshold shift in both ears was significantly higher among adults exposed than in the non-exposed in all tonal frequencies, except in the 500 hertz frequency in the right ear. Conclusions: the study provides a strong evidence of the adverse effects of the air traffic noise in the hearing ability of the exposed residents. The main impact is shown in the tonal frequency of 6.000 hertz. The non-exposed population also shows a high prevalence of hearing loss. Consequently, those institutions in charge of the public health must implement preventive and control measures.